Insecticidal and behavioral effects of essential oils on Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) - Bomfim, João Pedro A [UNESP]; Silva, Nadja N P [UNESP]; Marabesi, Marina O [UNESP]; Silva, Carolane B [UNESP]; Amaral, Jéssica C; Silva, Maria Fátima G F; Silva, Danielle F; Bonfim, Filipe P G [UNESP]; Oliveira, Regiane C [UNESP] (Oxford University Press (OUP), 2025)
Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is an agricultural pest of global importance, a vector of phytopathogens, with a wide distribution and a diverse range of hosts. The management of this pest primarily relies on synthetic insecticides; however, the selection pressure exerted by these products has led to the development of resistance to these molecules in 898 cases worldwide. Given the need to establish new management tactics for B. tabaci, this study aimed to evaluate the effect of essential oils (EOs) from Syzygium aromaticum (Myrtaceae), Cymbopogon citratus (Poaceae), Cordia verbenacea (Boraginaceae), Callistemon sp. (Myrtaceae), Baccharis dracunculifolia (Asteraceae), and Schinus terebinthifolius (Anacardiaceae) on the mortality of eggs, nymphs, and adults of B. tabaci Middle East Asia Minor 1 (MEAM1), as well as their repellent and oviposition deterrent effects on adults. The EOs of S. aromaticum and C. citratus were the most promising overall, exhibiting significant ovicidal activity, strong repellency, and deterrent effects on oviposition. Additionally, S. aromaticum and C. citratus EOs, and B. dracunculifolia EO, caused high nymphal mortality, while B. dracunculifolia EO stood out with the highest adult mortality. These findings highlight the potential of these EOs, particularly S. aromaticum and C. citratus, as multitarget tools within integrated pest management programs, offering environmentally friendly and effective alternatives for controlling B. tabaci MEAM1 across different developmental stages.